Beneficial and harmful effects of sacubitril/valsartan in patients with heart failure: a systematic review of randomised clinical trials with meta-analysis and trial sequential analysis. Issue 2 (30th November 2020) - Nielsen, Emil Eik; Feinberg, Joshua Buron; Bu, Fan-Long; Hecht Olsen, Michael; Raymond, Ilan; Steensgaard-Hansen, Frank; Jakobsen, Janus Christian
Abstract : Current guidelines recommend angiotensin receptor blocker neprilysin inhibitors (ARNI) (sacubitril/valsartan) as a replacement for angiotensin-converting-enzymeinhibitor (ACE-I) in heart failure with reduced ejection fraction (HFrEF) who remain symptomatic despite optimal medical therapy. The effects of ARNIs have not previously been assessed in a systematic review. We searched for relevant trials until October 2019 in CENTRAL, MEDLINE, Embase, LILACS, BIOSIS, CNKI, VIP, WanFang and CBM. Our primary outcomes were all-cause mortality and serious adverse events. We systematically assessed the risks of random errors and systematic errors. PROSPERO registration: CRD42019129336. 48 trials randomising 19 086 participants were included. The ARNI assessed in all trials was sacubitril/valsartan. ACE-I or ARB were used as control interventions. Trials randomising HFrEF participants (27 trials) and heart failure with preserved ejection fraction (HFpEF) participants (four trials) were analysed separately. In HFrEF participants, meta-analyses and Trial Sequential Analyses showed evidence of a beneficial effect of sacubitril/valsartan when assessing all-cause mortality (risk ratio (RR), 0.86; 95% CI, 0.79 to 0.94) and serious adverse events (RR, 0.89; 95% CI, 0.86 to 0.93); and the results did not differ between the guideline recommended target population and HFrEF participants in general. We found no evidence of an effect of sacubitril/valsartan in HFpEF participants. Sacubitril/valsartan compared with either ACE-I or ARB seems to have a beneficial effect in patients with HFrEF. Our results indicate that sacubitril/valsartan might be beneficial in a wider population of patients with heart failure than the guideline recommended target population. Sacubitril/valsartan does not seem to show evidence of a difference compared with valsartan in patients with HFpEF.